2018
DOI: 10.3389/fimmu.2018.00433
|View full text |Cite
|
Sign up to set email alerts
|

Viral miRNAs Alter Host Cell miRNA Profiles and Modulate Innate Immune Responses

Abstract: Prevalence of the members of herpesvirus family in oral inflammatory diseases is increasingly acknowledged suggesting their likely role as an etiological factor. However, the underlying mechanisms remain obscure. In our recent miRNA profiling of healthy and diseased human tooth pulps, elevated expression of human herpesvirus encoded viral microRNAs (v-miRs) were identified. Based on the fold induction and significance values, we selected three v-miRs namely miR-K12-3-3p [Kaposi sarcoma-associated virus (KSHV)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 66 publications
(74 reference statements)
3
44
0
1
Order By: Relevance
“…Interestingly, another contemporaneous study confirmed that exosomes released from NPC cells can enter into many types of host cells including epithelial, endothelial, and fibroblast cells, and modulating the tumor microenvironment to influence the cells growth by activating the ERK and AKT signaling pathways [97]. Besides EBV miRNAs, other herpesvirus miRNAs such as KSHV-encoded miRNAs were also observed in exosomes which were derived from KSHV positive cell lines and malignancies [19,98,99]. Moreover, following mechanism study revealed that KSHV-positive cells specifically deliver the KSHV-encoded miRNAs to neighboring cells through exosomes.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 93%
“…Interestingly, another contemporaneous study confirmed that exosomes released from NPC cells can enter into many types of host cells including epithelial, endothelial, and fibroblast cells, and modulating the tumor microenvironment to influence the cells growth by activating the ERK and AKT signaling pathways [97]. Besides EBV miRNAs, other herpesvirus miRNAs such as KSHV-encoded miRNAs were also observed in exosomes which were derived from KSHV positive cell lines and malignancies [19,98,99]. Moreover, following mechanism study revealed that KSHV-positive cells specifically deliver the KSHV-encoded miRNAs to neighboring cells through exosomes.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 93%
“…Additionally, similar to cellular miRNAs, viral miRNAs can also posttranscriptionally regulate numerous host genes. We recently showed that viral miRNAs can alter expression of both host mRNAs and miR-NAs in v-miR expressing oral keratinocytes and myeloid cells (macrophages) (Naqvi, Seal, Shango, Brambila, et al, 2018;Naqvi, Seal, Shango, Shukla, et al, 2018;Naqvi, Shango, Seal, Shukla, & Nares, 2018a). These widespread v-miR-mediated transcriptome changes can affect numerous cellular functions including immune responses, phagocytosis and cell migration.…”
Section: Studies From Various Groups Including Ours Have Demonstratedmentioning
confidence: 99%
“…According to a recent report, HCMV expresses miR-UL70-3p and miR-UL148D to target the apoptotic genes MOAP1, ERN1, and PHAP1 and to inhibit mitochondriainduced apoptosis aa well as the antiviral mechanism [29]. Besides, miR-UL70-3p may regulate focal adhesions, gap junctions, MAPK signaling, and the Erb pathway, thus affecting epithelial cell migration and adhesion [70]. Another recent report has discovered 14 mature HCMV miRNAs in infected human lung fibroblasts, including miR-UL70-5p, indicating that HCMV virions and dense bodies carry miRNAs (such as miR-UL70-5p) which can be delivered to cells to affect cellular processes [71].…”
Section: Mir-ul59 Mir-ul69 and Mir-ul70mentioning
confidence: 99%